Preparation method and application of catalytic packing and conversion method of catalytic rectifying tower
Patent Information
- Application Number
- CN202410774567.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-17
- Publication Date
- 2026-10-20
- Estimated Expiration
- 2044-06-17
AI Technical Summary
[0007]本发明针对现有催化填料的催化层不耐磨和耐热问题,而提供一种耐磨、耐热的催化填料的制备方法及应用
[0053]本发明的催化填料在制备时引入磁性材料,能够大大改善催化填料的耐磨性和耐热性,特别是对于金属填料载体,引入的磁性材料通过磁性吸附力帮助环氧树脂胶层与金属填料载体结合更加牢固,增加环氧树脂胶层与金属填料载体之间的作用力以提高催化层的整体附着性,三者协同作用下,有助于提高催化填料的使用寿命。
Smart Images

Figure CN118681248B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a method for preparing catalytic packing, its application, and a conversion method for catalytic distillation columns. Background Technology
[0002] Catalytic distillation is a chemical process that couples chemical reactions with distillation, significantly improving reaction efficiency. Currently, catalytic distillation is mainly applied to hydrolysis, esterification, transesterification, etherification, and alkylation. Propionic acid is an important raw material for fine and basic chemicals. Catalytic distillation can greatly improve the efficiency of methyl propionate hydrolysis, thereby reducing propionic acid production costs. Other propionic acid isoesters or methacrylate isoesters, used in fragrances and flavorings as well as material processing aids, benefit greatly from catalytic distillation in terms of transesterification efficiency. However, the method of catalyst loading has a significant impact on the catalytic distillation process.
[0003] Currently, the combination of packing and catalyst in catalytic distillation technology mainly consists of the following three methods: (1) Non-fixed packing: mechanical mixing packing, where triangular springs or θ rings are mixed with resin in a certain proportion and then packed. In this method, since the resin and packing are not fixed, they will gradually separate as the gas and liquid materials flow, reducing the catalytic effect; (2) Physically fixed packing: the resin is packaged with cloth or stainless steel wire mesh and then fixed with the wire mesh packing, or the two are stacked and rolled into a concentric cylindrical shape, or the two are placed alternately in parallel to form a sandwich-type structured packing. Stainless steel wire mesh has better material permeability and faster mass transfer than cloth, so the current industrial structured packing is mainly a sandwich type of stainless steel wire mesh resin package and wire mesh packing; (3) Integrated composite packing: the catalyst and packing are combined to directly form a catalytic packing with active groups on the surface. Current technological improvements are mainly focused on two directions: physical fixed packing of resin and packing and integrated composite packing, with integrated composite packing being the main approach.
[0004] For example, patent CN111013173B describes a supported catalytic packing, its preparation method, and its application. This method involves dissolving a porous medium in a porogen, adding a crosslinking agent to form an adhesive, immersing the packing carrier in the adhesive, removing it, and curing it to obtain a packing carrier containing a cured adhesive layer. The porogen in the adhesive layer is removed, and after vacuum drying, a packing carrier with a porous adhesive layer is obtained. This is then placed in a PSS-Na aqueous solution, allowing PSS-Na to penetrate the micropores of the adhesive layer and react with the resin. Finally, it is acidified in a dilute sulfuric acid solution, washed with water to remove residual acid, and vacuum dried to obtain the supported catalytic packing. Patent CN113198535B describes a method for preparing a ceramic surface supported catalytic packing. However, the adhesion, wear resistance, and heat resistance of this supported catalytic packing need improvement.
[0005] Patent CN114989484B describes a method for preparing a supported catalytic packing for reactive distillation. It utilizes the oxidative crosslinking of tannic acid and a silane coupling agent under weakly alkaline conditions, and the hydroxyl groups on the ceramic surface that can be reacted with the coupling agent. An active layer is designed on the surface of a commercial ceramic packing, and an imidazole solid acid catalyst is grafted in situ to obtain the supported catalytic packing. However, this supported catalytic packing does not address its wear resistance and heat resistance.
[0006] In summary, existing supported catalytic packing materials do not address wear resistance and heat resistance. Furthermore, for metal packing supports, the process involves forming an adhesive layer on the surface, coupling it with an organic polymer carrying metal ions, and then acidifying it to form the catalytic layer (e.g., patent CN114989484B). These types of catalytic packing materials are prone to catalytic layer detachment during use, resulting in poor adhesion, reduced catalytic efficiency, and significantly shortened lifespan. Moreover, existing catalytic packing materials are all treated outside the tower before loading, which involves complex procedures, requires extensive production equipment and instruments, and necessitates complete replacement of the entire catalytic packing material once it reaches its service life in actual production. Summary of the Invention
[0007] This invention addresses the problems of poor wear and heat resistance in existing catalytic packing layers by providing a method for preparing and applying a wear-resistant and heat-resistant catalytic packing. Specifically, for metal packing supports, it also increases adhesion, solving the problem of easy catalytic layer detachment. The synergistic effect of wear resistance, heat resistance, and high adhesion significantly improves the catalytic reaction efficiency and lifespan of the catalytic packing.
[0008] To achieve the above objectives, the technical solution adopted by the present invention is as follows:
[0009] A method for preparing a catalytic packing material includes the following steps:
[0010] (1) The packing carrier is loaded into the reaction equipment;
[0011] (2) The epoxy resin solution is introduced into the reaction equipment and circulated, and discharged after circulation is completed, so that a liquid film is formed on the surface of the filler carrier. The epoxy resin solution includes solvent, epoxy resin, magnetic material, curing agent and first monomer.
[0012] (3) Heating reaction causes the epoxy resin to crosslink and cure, forming an epoxy resin adhesive layer on the surface of the filler carrier;
[0013] (4) The second monomer solution is introduced into the reaction equipment and circulated. After circulation is completed, it is discharged, so that a liquid film is formed on the surface of the epoxy resin adhesive layer.
[0014] (5) The initiator solution is introduced into the reaction equipment to initiate the polymerization reaction and then discharged, wherein the initiator solution contains an initiator and a magnetic material;
[0015] (6) Increase the temperature to ensure the polymerization reaction is complete;
[0016] (7) Acid solution is passed into the reaction equipment to acidify and obtain a catalytic packing material with active catalytic components on the surface.
[0017] In this invention, the catalytic filler prepared by adopting the above technical solution includes a filler carrier and a catalytic layer covering the filler carrier. The catalytic layer includes an epoxy resin adhesive layer and active catalytic components bonded to the surface of the epoxy resin adhesive layer. Magnetic materials are distributed in the epoxy resin adhesive layer and / or attached to the surface of the epoxy resin adhesive layer. The magnetic materials may also be embedded in a polymer framework structure with active catalytic components.
[0018] According to some embodiments of the present invention, the reaction apparatus is a distillation column. The preparation of the catalytic packing is carried out within the column, enabling the composite catalytic layer of conventional packing. Furthermore, the catalytic layer does not need to be replaced after failure; it can be directly regenerated and repaired within the column, reducing the disposal of used and failed catalytic packing and the repacking of new packing. This allows for the reuse of the packing and significantly reduces intermediate costs. In addition, the preparation of the catalytic packing within the column also allows for the formation of a catalytic layer on the inner wall of the column, providing both metal corrosion protection and incidental catalysis. Moreover, regarding material corrosion protection, the corrosion resistance level of the packing carrier can be reduced by one level, thereby lowering the cost of the packing carrier.
[0019] According to some embodiments of the invention, the reaction apparatus may also be a series of other equipment containers that can replace the distillation column to complete the packing transformation, the series of other equipment containers including a combination of one or more of tanks, pumps, thermostats, and drying ovens.
[0020] According to some embodiments of the present invention, the active catalytic component is one or a combination of several of polystyrene sulfonic acid, modified polystyrene sulfonic acid, etc.
[0021] According to some embodiments of the present invention, the magnetic material is a magnetic nanomaterial, and further, the magnetic material is one or a combination of magnetic iron oxide, ferrite materials, magnetic metals and their alloys; the metal is one or a combination of iron, cobalt, nickel, etc.; preferably, magnetic iron oxide nanomaterials.
[0022] There are no particular restrictions on the preparation of the magnetic nanomaterials into solutions; conventional preparation methods used in the field, such as ultrasonic dispersion, can be employed.
[0023] In some specific embodiments, the first monomer is one or a combination of styrene and divinylbenzene, and the second monomer is sodium p-styrene sulfonate. The styrene can complete most of the crosslinking reaction in the epoxy resin adhesive layer and can leave active crosslinking sites on the surface of the epoxy resin adhesive layer. This allows for the reactivation of incompletely crosslinked styrene or fully crosslinked polystyrene ends under the action of a subsequent initiator, thereby enabling the graft polymerization of sodium p-styrene sulfonate. This helps to improve the bonding between the active catalytic component and the epoxy resin adhesive layer.
[0024] In some specific embodiments, a modifier may be selectively added to the second monomer solution. The modifier is either a hydrophilic or lipophilic monomer. The addition of the modifier is primarily to increase the affinity between the catalyst layer and the reactants, thereby improving the reaction rate. To increase the hydrophilicity of the catalyst layer, polymerizable monomers with more hydroxyl or carboxyl groups are selected as modifiers; to increase the lipophilicity of the catalyst layer, polymerizable monomers with more methyl groups are selected. For some ester hydrolysis reactions, which require both hydrophilicity and lipophilicity, modifiers such as methacrylic acid can be selected. These polymerizable acidic modifiers can crosslink onto the matrix, altering the hydrophilicity or lipophilicity while also providing a weak auxiliary catalytic effect.
[0025] In some specific embodiments, the second monomer solution contains 15-20% by mass of the second monomer, and the second monomer solution also selectively contains 1-3% of a modifier, with the remainder being solvent.
[0026] According to some embodiments of the present invention, the material of the filler carrier is one or a combination of several of the following: metal, plastic, ceramic, glass, fiberglass, rubber, etc.
[0027] In some specific embodiments, the packing carrier is made of metal, and the preparation method further includes the steps of introducing a rust-removing liquid into the reaction equipment for rust removal and then introducing water for washing before introducing the epoxy resin solution into the reaction equipment. After rust removal and water washing, a small amount of nitrogen is introduced to maintain a slight positive pressure inside. For metal packing carriers, foreign matter or oxide layers may remain on the surface; removing rust from these layers helps improve the adhesion of the catalyst layer to the packing carrier.
[0028] There are no particular restrictions on the specific composition and rust removal time of the rust remover; any rust remover and rust removal time conventionally used in this field can be used. For example, a rust remover can be prepared by mixing a 20% sulfuric acid aqueous solution, acrylic acid, sodium dodecyl sulfonate, hexamethylenetetramine, and polyethylene glycol in a mass ratio of 50:2–8:2–8:0.2–1.5:0.2–1.5, and then circulating it for rust removal for 20 ± 5 minutes. Alternatively, a rust remover can be prepared by mixing a 20% sulfuric acid aqueous solution, acrylic acid, sodium dodecyl sulfonate, hexamethylenetetramine, and polyethylene glycol in a mass ratio of 50:5:5:1:1, and then circulating it for rust removal for 20 minutes.
[0029] The step of rinsing with water can be achieved by replacing the rust-removing solution with the corresponding amount of water, pumping the water into the distillation column for circulation, and rinsing for 2 minutes. Alternatively, the rinsing time can be calculated based on the packing height, with a rinsing time of 2 minutes per meter.
[0030] According to some embodiments of the present invention, the packing carrier is a structured packing or a random packing. Further, the packing carrier is one or a combination of several of the following: random packing such as Sital rings, Raschig rings, and triangular springs; or structured packing such as perforated corrugated plates, wire mesh, and helical springs.
[0031] In some specific embodiments, in step (2), the circulation time is 5 to 15 minutes, or calculated based on the packing height, the circulation time is 3 to 5 minutes per meter, and the circulation is carried out at 50 to 70 degrees Celsius.
[0032] In some specific embodiments, the preparation method further includes, after the circulation in step (2) is completed, purging the reaction equipment with inert gas at a temperature of 50–70°C for 1–3 minutes. Purging with inert gas after the epoxy resin solution circulation is completed helps to obtain an epoxy resin adhesive layer of uniform thickness.
[0033] In some specific embodiments, the epoxy resin solution contains 5-20% by mass of epoxy resin, 3-5% by mass of the first monomer, 0.01-1% by mass of the magnetic material, 2-6% by mass of the curing agent, and the remainder is solvent.
[0034] The epoxy resin is one or a combination of bisphenol A type epoxy resin and phenolic epoxy resin, and the curing agent is one or a combination of m-phenylenediamine, ethylenediamine, etc. The solvent used in the epoxy resin / phenolic resin solution is ethanol.
[0035] In some specific embodiments, the preparation method further includes step (3), in which the temperature of the heating reaction is 80-110°C, and during the heating reaction, the reaction equipment is purged with an inert gas for more than 2 hours to allow the solvent to evaporate rapidly, forming an irregular surface and causing the resin to crosslink and cure. Further, in step (3), the purging time is 2-7 hours, and the inert gas is nitrogen.
[0036] In some specific embodiments, in step (6), the temperature of the heating reaction is 90–120°C. During the heating reaction, the reaction equipment is purged with an inert gas for more than 7 hours to allow the solvent to evaporate, forming an irregular surface and cross-linking and curing it. Further, in step (6), the purging time is 7–12 hours, and the inert gas is nitrogen.
[0037] In practice, the inventors had tried adding a pore-forming agent to the epoxy resin solution, which resulted in increased costs. However, by using step (3) to raise the temperature to 80-110°C and purging with inert gas for a long time, and step (6) to raise the temperature to 90-120°C and purging with inert gas for a long time, the solvent on the filler surface evaporates rapidly, causing the outer resin / catalytic layer to burst. This helps to form a porous or uneven effect on the filler surface, increasing the specific surface area, enabling the binding of more catalytically active substances, and improving catalytic efficiency.
[0038] In some specific embodiments, in step (4), the cycle time is 5 to 10 minutes, and the cycle is carried out at 50 to 70°C.
[0039] In some specific embodiments, the preparation method further includes, after the second monomer solution is discharged in step (4), an inert gas is introduced into the reaction equipment for purging, the purging temperature is 50-70°C, and the purging time is 1-3 min.
[0040] In some specific embodiments, in step (5), after the initiator solution is discharged, the system is maintained at 50-70°C for 1-3 hours to react.
[0041] In some specific embodiments, the initiator solution contains 0.1-0.3% by mass of the initiator, 0.01-1% by mass of the magnetic material, and the remainder is solvent. The initiator is a free radical initiator, such as one or a combination of several of azobisisobutyronitrile (AIBN) and di-tert-butyl peroxide. The solvent used in the initiator solution is ethanol.
[0042] In some specific embodiments, the preparation method further includes, after the initiator solution in step (5) is discharged, purging the reaction equipment with inert gas, the purging temperature being 50-70°C and the purging time being 1-3 min.
[0043] In some specific embodiments, the preparation method further includes repeating steps (4) to (5) 2 to 3 times.
[0044] In some specific embodiments, in step (7), the acid solution is circulated into the reaction equipment, and the circulation time is 0.5 to 1 hour.
[0045] The acid solution is a sulfuric acid solution with a mass concentration of 3-5%, and other inorganic or organic strong acids such as nitric acid, hydrochloric acid, and trifluoromethanesulfonic acid that can provide an equal amount of hydrogen ions.
[0046] In some specific embodiments, the preparation method further includes step (7), in which water is introduced into the reaction equipment for washing after the acidification is completed, the washing time is 10-30 min, or calculated according to the height of the packing, the washing time is 10-30 min / m.
[0047] The second technical solution adopted by the present invention is a method for converting a conventional distillation column into a catalytic distillation column, which includes the step of preparing catalytic packing material in the distillation column using the preparation method of the catalytic packing material described above.
[0048] The third technical solution adopted in this invention is: a catalytic packing prepared by the above-mentioned method is used in a reactive distillation process, wherein the reactive distillation process includes hydrolysis reaction, transesterification reaction, esterification reaction, etherification reaction, alkylation reaction, isomerization reaction, acylation reaction, olefin addition reaction, olefin hydration reaction, and dehydration condensation reaction.
[0049] In some specific embodiments, the hydrolysis reaction includes the reaction of ester hydrolysis into acid.
[0050] In some specific embodiments, the transesterification reaction includes a reaction in which an ester reacts with an alcohol to produce an isoester and an isool.
[0051] The esters include methyl propionate and methyl methacrylate.
[0052] Due to the application of the above technical solution, the present invention has the following advantages compared with the prior art:
[0053] The catalytic packing of the present invention incorporates magnetic materials during preparation, which can greatly improve the wear resistance and heat resistance of the catalytic packing. In particular, for metal packing carriers, the introduced magnetic materials help the epoxy resin adhesive layer and the metal packing carrier to bond more firmly through magnetic adsorption force, and increase the interaction force between the epoxy resin adhesive layer and the metal packing carrier to improve the overall adhesion of the catalytic layer. The synergistic effect of these three factors helps to improve the service life of the catalytic packing. Attached Figure Description
[0054] Figure 1 This is a scanning electron microscope image of the surface of the catalytic packing obtained in Example 1. Detailed Implementation
[0055] To address the issues of poor wear and heat resistance in existing catalytic packing materials, as well as the tendency for metal packing catalyst layers to detach, the main concept of this invention lies in introducing magnetic materials into the catalyst layer. This significantly improves the wear and heat resistance of the catalyst layer, particularly for the metal packing support. Magnetic adsorption forces are used to create a stronger bond between the catalyst layer and the metal packing support. The synergistic effect of these three elements greatly enhances the catalytic reaction efficiency and lifespan of the catalytic packing material.
[0056] Traditional catalytic packing materials are prepared outside the distillation column, involving complex steps and requiring extensive production equipment and instruments. Furthermore, the catalytic packing materials must be replaced entirely once they reach their service life during actual production. The present invention further proposes that the catalytic packing material is prepared by loading a packing carrier into a distillation column. All operations are carried out inside the column. Conventional distillation columns have a lifespan of at least ten to fifteen years in industrial production, but the catalyst layer cannot reach such a long lifespan, requiring replacement of the entire catalytic packing material within one to three years. This invention, however, places the entire process of repairing and regenerating the catalyst layer inside the column. This reduces the need for handling spent and ineffective catalytic packing materials and reloading with new materials, allowing for the reuse of the packing material and significantly reducing intermediate costs.
[0057] In this invention, the circulation method is not particularly limited and can be any circulation method conventionally used in the art, such as spraying or immersion. When the circulation method is spraying, the spray density can be 1–10 m³ / s. 3 / (m 2 (·h). The spray density can be fixed throughout the process or adjusted adaptively according to different cycle times, as long as the cycle requirements are met. It should be noted that for loose packing, the spray density can be set to 1–5 m³ / h. 3 / (m 2 If the spraying time is longer (e.g., 4-10 m), then the corresponding spraying time will be extended, while the spraying time for industrially produced structured fillers is 4-10 m. 3 / (m 2 ·h), the spraying time can be shortened.
[0058] The technical solutions of the present invention will be described in detail below with reference to specific embodiments, so that those skilled in the art can better understand and implement the technical solutions of the present invention, but the present invention is not limited to the scope of the examples described.
[0059] Example 1
[0060] This embodiment provides a method for converting a conventional distillation column into a catalytic distillation column, as follows:
[0061] (1) Stainless steel wire mesh packing is rolled into a cylindrical shape and placed in the middle of a DN25×1400mm stainless steel distillation column. The packing length is 1000mm, and an electric heating tape is wrapped around the outside. The spray density is set to 4m³ / h throughout the entire process. 3 / (m 2 ·h);
[0062] (2) A rust removal solution was prepared by mixing 20% sulfuric acid aqueous solution, acrylic acid, sodium dodecyl sulfonate, hexamethylenetetramine and polyethylene glycol in a mass ratio of 50:5:5:1:1. The rust removal solution was circulated into the distillation column at room temperature by pumping for 20 minutes.
[0063] (3) Replace the rust remover with the corresponding amount of water, and use a pump to pump the water into the distillation column for circulation. The water washing time is 2 minutes. After the water washing is completed, nitrogen gas is continuously introduced to drain the water from the bottom to ensure that the column is under a slight positive pressure and that air does not enter.
[0064] (4) Preparation of epoxy resin solution: Add magnetic iron oxide nanopowder to anhydrous ethanol and sonicate for 20 min to uniformly disperse the magnetic iron oxide nanopowder in anhydrous ethanol to obtain iron oxide ethanol solution. Then add bisphenol A type epoxy resin, m-phenylenediamine and styrene and mix to obtain epoxy resin solution. The mass concentration of bisphenol A type epoxy resin is 15%, the mass concentration of styrene is 4%, the mass concentration of iron oxide is 0.1%, and the mass concentration of m-phenylenediamine is 3%.
[0065] (5) Pump the epoxy resin solution into the distillation column and circulate it for 8 minutes. Then drain the liquid and remove any residue. Purge the packing in the column from top to bottom with nitrogen for 2 minutes to ensure that there is no liquid accumulation in the packing and that there is a liquid film remaining. The temperature is maintained at 60°C throughout the process.
[0066] (6) Raise the temperature to 90°C and purge with nitrogen for 5 hours to allow the ethanol on the filler surface to boil and evaporate rapidly to form an irregular surface, increase the surface area, and allow the epoxy resin to cross-link and cure.
[0067] (7) Preparation of sodium p-styrene sulfonate aqueous solution: Sodium p-styrene sulfonate and water are mixed, and then methacrylic acid is added and mixed to obtain sodium p-styrene sulfonate aqueous solution, wherein the mass concentration of sodium p-styrene sulfonate is 18% and the mass concentration of methacrylic acid is 2%.
[0068] (8) Preparation of initiator solution: Add magnetic iron oxide nanopowder to anhydrous ethanol and sonicate for 20 min to uniformly disperse the magnetic iron oxide nanopowder in anhydrous ethanol to obtain iron oxide ethanol solution. Then add azobisisobutyronitrile and mix to obtain initiator solution, wherein the mass concentration of azobisisobutyronitrile is 0.2% and the mass concentration of iron oxide is 0.1%.
[0069] (9) Pump the sodium styrene sulfonate aqueous solution into the distillation column and spray it for 8 minutes. Then drain the liquid and purge it from top to bottom with nitrogen for 2 minutes to ensure that there is no liquid accumulation in the packing and that there is a liquid film remaining. The temperature is maintained at 70°C throughout the process.
[0070] (10) Pump the initiator solution into the distillation column and spray for 1 minute, then stop spraying to initiate the polymerization reaction. The temperature is maintained at 70℃ for 2 hours throughout the process.
[0071] (11) Repeat steps (9) and (10) twice, then raise the temperature to 110°C and purge with nitrogen for 10 hours to allow the ethanol on the filler surface to boil and evaporate rapidly to form an irregular surface, increase the surface area, and complete the cross-linking and curing process.
[0072] (12) Prepare acid solution: Mix sulfuric acid and water to prepare a 4% sulfuric acid solution, then pump it into the tower for circulation spraying for 1 hour until all the salt is converted into acid, and then drain the acid solution.
[0073] (13) Pump water into the tower and circulate it for 20 minutes to wash away the residual acid and obtain the catalytic packing, thus completing the conversion of the conventional distillation tower into an integrated catalytic distillation tower.
[0074] Example 2
[0075] The method for converting a conventional distillation column into a catalytic distillation column provided in this embodiment is basically the same as in Embodiment 1, except that:
[0076] In step (1), plastic filler is used.
[0077] Step (2) is omitted.
[0078] In step (3), a 20% ethanol aqueous solution is used for 10 min of cyclic washing.
[0079] Example 3
[0080] The method for converting a conventional distillation column into a catalytic distillation column provided in this embodiment is basically the same as in Embodiment 1, except that:
[0081] In step (1), ceramic filler is used.
[0082] Step (2) is omitted.
[0083] In step (3), a 20% ethanol aqueous solution is used for 10 min of cyclic washing.
[0084] Example 4
[0085] The method for converting a conventional distillation column into a catalytic distillation column provided in this embodiment is basically the same as in Embodiment 1, except that:
[0086] In step (1), random packing material and 3mm×3mm stainless steel triangular springs are used. The spray density is set to 2.5m throughout the process. 3 / (m 2 ·h)
[0087] Comparative Example 1
[0088] The catalytic distillation column provided in this comparative example is obtained by filling the middle of a DN25×1400mm stainless steel distillation column with a conventional stainless steel wire mesh resin pack and a triangular spring in a 1:1 volume ratio, with a filling length of 1000mm.
[0089] Comparative Example 2
[0090] This comparative example provides a method for converting a conventional distillation column into a catalytic distillation column, which is basically the same as in Example 1, except that the addition of nano-Fe3O4 in steps (4) and (8) is omitted.
[0091] Comparative Example 3
[0092] This comparative example provides a method for converting a conventional distillation column into a catalytic distillation column, which is basically the same as in Example 1, except that the temperature in step (6) is 60°C and the temperature in step (11) is 70°C.
[0093] Comparative Example 4
[0094] This comparative example provides a method for converting a conventional distillation column into a catalytic distillation column, which is basically the same as in Example 1, except that styrene is not added in step (4).
[0095] Comparative Example 5
[0096] This comparative example provides a method for converting a conventional distillation column into a catalytic distillation column, which is basically the same as in Example 1, except that step (2) is omitted.
[0097] Comparative Example 6
[0098] The method for converting a conventional distillation column to a catalytic distillation column provided in this comparative example is basically the same as in Example 1, except that:
[0099] In step (5), the circulation time is 2 minutes and the purging time is 6 minutes;
[0100] In step (9), the circulation time is 2 minutes and the purging time is 6 minutes;
[0101] In step (10), the spraying time is 1 hour after the spraying ends.
[0102] Comparative Example 7
[0103] The method for converting a conventional distillation column to a catalytic distillation column provided in this comparative example is basically the same as in Example 1, except that:
[0104] In step (5), the circulation time is 25 min and the purging time is 0.5 min;
[0105] In step (9), the circulation time is 25 min and the purging time is 0.5 min;
[0106] In step (10), the spraying time is 3 hours after the spraying ends.
[0107] Comparative Example 8
[0108] The method for converting a conventional distillation column to a catalytic distillation column provided in this comparative example is basically the same as in Example 1, except that:
[0109] In step (7), no methacrylic acid is added.
[0110] Performance testing
[0111] 1. SEM characterization
[0112] The catalytic packing material obtained in Example 1 was scanned using a JEOL JSM 6701-F scanning electron microscope, and the results are as follows: Figure 1 As shown, numerous porous structures were observed on its surface at the micrometer level. It is speculated that this effect is due to the rapid boiling and evaporation of ethanol caused by raising the temperature to high and purging with nitrogen gas in steps (6) and (11). The surface area of the packing material is greatly increased, allowing it to support more acidic sites and improve the catalytic rate.
[0113] 2. TG and DSC testing
[0114] The commonly used styrene resin and the catalytic packing materials obtained in Example 1 and Comparative Example 2 were tested using a NETZSCH STA449F3 thermogravimetric analyzer and a NETZSCH DSC 204F1 DSC. It was found that the glass transition temperature of the catalytic packing material in Example 1 was increased by nearly 20°C. The Tg of conventional polystyrene resin is 100°C, but the Tg of the catalytic packing material in Example 1 is 119°C, which is 17°C higher than that in Comparative Example 2. This indicates that the addition of nano-ferric oxide improves the thermal stability of the polymer catalytic layer.
[0115] 3. Abrasion resistance test
[0116] A certain amount of conventional polystyrene resin and the catalytic filler obtained in Examples 1-3 and Comparative Example 2 were weighed and placed into grinding jars using a YXQM planetary ball mill and grinding ceramic balls, respectively, and ground at a certain rate for the same amount of time. After removal, the resin grinding jar contained a large number of pulverized particles, forming a suspension; while the materials in Examples 1-3 showed almost no detached particles in the grinding jar, and Comparative Example 2 contained a small number of larger particles. After filtering the pulverized particles, drying, and weighing, the mass loss rate of the resin after grinding was 20-30% higher than that of the materials in Examples 1-3, and the mass loss rate of Comparative Example 2 was also 15% higher than that of Examples 1-3. The reason for this is that the addition of nano-metals improves the wear resistance of the materials.
[0117] 4. Shedding rate test
[0118] The catalytic packing materials of Examples 1-3 and Comparative Examples 2, 4-5 were treated with an ultrasonic oscillator at a frequency of 200 kHz. The solution system consisted of methyl propionate, water, methanol, and propionic acid in a mass ratio of 6:1:2:1. The corresponding oscillation time and shedding rate are shown in Table 1. The shedding rate was calculated as follows:
[0119] Shedding rate = (m1 - m2) / ((m1 - m0))
[0120] m0: Initial mass of the packing
[0121] m1: Quality of the catalytic packing with a well-supported catalytic layer
[0122] m2: Mass of the catalytic packing material after oscillation.
[0123] Table 1 shows the shedding rate of the catalyst packing materials in Examples 1-3 and Comparative Examples 2, 4-5.
[0124] Oscillation time / h Shedding rate / % Shedding rate / % Shedding rate / % Shedding rate / % Shedding rate / % Shedding rate / % 2 0 0 0 0 0.53 1.05 4 0 0 0 0.44 1.18 / 8 0 0 0 0.95 / / 12 0 0 0 2.31 / / 24 0.95 0 0 5.20 / / 36 2.25 0.51 0.83 7.48 / / 48 4.89 1.3 2.15 12.15 / /
[0125] As shown in Table 1, the rate of detachment accelerates once the catalyst layer begins to peel off. Due to the presence of organic esters, alcohols, and acids in the system, the catalyst layer can stably adhere to the metal surface when intact; however, once the catalyst layer begins to break down, both the detachment rate and the detachment speed (the detachment speed is the difference in detachment rates divided by the corresponding time difference) increase. The detachment rate of Comparative Example 2 is significantly higher than that of Example 1, presumably because the addition of nanomaterials increases the adhesion of the catalyst layer. In Examples 2 and 3, when plastic or ceramic is used as the substrate, the detachment rate is lower than that of the metal substrate, likely because epoxy resin bonds more easily to the plastic / ceramic substrate. Comparative Examples 4 and 5 show very high detachment rates after 4 hours or 2 hours, with detachment speeds far exceeding those of other examples and comparative examples; therefore, further experimentation is unnecessary, and the experiments are discontinued.
[0126] 5. Verification of reaction effect
[0127] The catalytic distillation columns of Example 1 and Comparative Example 1 were applied to the hydrolysis of methyl propionate to produce propionic acid. The catalytic section of the catalytic distillation column was opened at both ends, and two reaction materials (methyl propionate and water were fed in a molar ratio of 1:1) were introduced from the upper and lower ends of the catalytic section respectively, and the reaction was carried out on the catalytic section. The reaction results are shown in Table 2.
[0128] Table 2 shows the reaction effects of using the catalytic distillation columns of Example 1 and Comparative Example 1 on the hydrolysis of methyl propionate to produce propionic acid.
[0129]
[0130] *Catalytic life is the percentage of the production capacity in the second month to the production capacity in the first month after the catalytic distillation column has been running continuously for two months.
[0131] As shown in Table 2, the catalytic distillation column of Example 1, when used for the hydrolysis of methyl propionate, mainly exhibits reduced pressure drop. The original resin-coated channel was replaced by packing sheets. Although the liquid holdup decreased, the throughput increased. This is likely because gas-liquid mass transfer is hindered in the resin-coated channel of a conventional catalytic distillation column (Comparative Example 1), while in Example 1, the catalytic layer is located on the surface of the packing and is uniformly distributed, making gas-liquid mass transfer relatively easier. Furthermore, regarding the maximum reaction temperature, conventional resins require temperatures below 120°C, and exceeding 100°C is not recommended, determined by the Tg of polystyrene. In Example 1, the addition of nano-ferric oxide increases the maximum reaction temperature (hydrolysis is endothermic, and pressurization and heating facilitate the reaction), thus increasing the reaction rate and single-pass conversion (reducing the proportion of reactants in the azeotropic distillation at the top of the column). In terms of catalytic lifespan, Example 1 is slightly better due to the shorter experimental time, but the difference is not significant. If the experimental time is extended, the catalytic lifespan of Example 1 will be significantly better than that of Comparative Example 1.
[0132] The catalytic packed tower of Example 1 and the catalytic packed towers of Comparative Examples 2 and 3 were used for the hydrolysis of methyl propionate, and the reaction results are shown in Table 3.
[0133] Table 3 shows the reaction effects of using the catalytic distillation columns of Examples 1 and 2-3 in the hydrolysis of methyl propionate to produce propionic acid.
[0134]
[0135] As shown in Table 3, Comparative Example 2 is similar to Example 1 in terms of pressure drop, liquid holdup, and throughput. However, due to the maximum temperature, its highest conversion rate is lower than that of Example 1, and its lifespan begins to show deficiencies. Compared to Comparative Example 3, Example 1 has a methyl propionate conversion rate of 76.8%, while Comparative Example 3 has a methyl propionate conversion rate of 65.2%. This demonstrates that the surface area increase treatment in Example 1 is crucial. Meanwhile, the pressure drop of Comparative Example 3 is slightly lower than that of Example 1, and the liquid holdup of Comparative Example 3 is only about 40% of that of Example 1.
[0136] The catalytic packed tower of Example 1 and the catalytic packed towers of Comparative Examples 6-8 were used for the hydrolysis of methyl propionate, and the reaction results are shown in Table 4.
[0137] Table 4 shows the reaction effects of using the catalytic distillation columns of Examples 1 and Comparative Examples 6-8 in the hydrolysis of methyl propionate to produce propionic acid.
[0138]
[0139] As shown in Table 4, the methyl propionate conversion rate of Comparative Example 6 was significantly lower than that of Example 1. This is presumably due to the shorter cycle time and longer purging time, resulting in a thinner catalyst layer and insufficient active catalyst loading. This was confirmed by subsequent determination of the exchange capacity of active molecules using the same acid-base titration method. Similarly, the methyl propionate throughput of Comparative Example 7 was significantly lower than that of Example 1. This is presumably due to the longer cycle time and shorter purging time, resulting in a thicker catalyst layer that may have blocked most of the pores. This was confirmed by subsequent disassembly and extraction. In Comparative Example 8, the lack of methacrylic acid reduced the affinity of the catalyst layer for the material, resulting in a slightly lower methyl propionate conversion rate than in Example 1.
[0140] Examples 2-4 showed no significant difference in reaction effects compared to Example 1, so they will not be described in detail.
[0141] In summary, the representative embodiments of the present invention have the following advantages compared with traditional resin-coated packed distillation columns:
[0142] (1) Compared with the traditional technology of producing resin first and then assembling it with filler, the present invention processes existing commercial fillers, random packing or structured packing, especially metal fillers, so that they have both reaction and separation functions. This not only shortens the intermediate steps, but also improves the utilization rate of catalytic active groups and reduces the cost of catalytic fillers.
[0143] (2) Compared with the conventional technique of mixing resin packaging and filler, the integrated catalytic filler obtained in the embodiments of the present invention has a smaller relative volume, faster reaction rate, smaller pressure drop, and larger processing capacity.
[0144] (3) Compared with resin catalyst packs, the embodiments of the present invention have a high degree of adhesion between the catalyst layer and the packing carrier (especially the metal packing carrier), and there is no friction between the catalyst packings that would cause wear, thus extending the service life of the catalyst packings.
[0145] (4) Compared with the catalytic packing technology that is simply physically coated, the embodiments of the present invention add magnetic materials to the catalytic layer, which makes the two more firmly bonded and improves the heat resistance and wear resistance of the catalytic layer. Under the synergistic effect of the three, the catalytic packing has a longer service life.
[0146] (5) In accordance with the requirements of the embodiments of the present invention, the mesh size of the metal wire mesh packing (20 to 200 mesh) or the size of the random packing and the thickness of the chemically coated surface catalyst layer (a few micrometers to tens of micrometers) can be changed to a certain extent to adjust the separation and catalytic effect. In addition, the catalyst layer thickness can be controlled in a regulated manner to achieve the best technical effect.
[0147] (6) In the embodiments of the present invention, all operations are designed to be carried out in a conventional distillation column, which can be converted into a catalytic distillation column. Furthermore, the catalytic layer can be regenerated in the column after the catalytic packing fails, without having to replace the entire failed catalytic packing, which greatly reduces the replacement cost and waste solids treatment cost.
[0148] Using the catalytic distillation column of the representative embodiment of the present invention for propionic acid production has the following advantages: high raw material utilization rate, high single-pass conversion rate of methyl propionate, no by-products, simple separation, and high purity of propionic acid; the metal surface is coated with a polymer organic catalyst layer, which avoids direct contact between the metal and the acid and slows down metal corrosion; due to the improved heat resistance of the catalyst layer, the maximum reaction temperature can be appropriately increased, thereby increasing the single-pass conversion rate of methyl propionate.
[0149] The above embodiments are only for illustrating the technical concept and features of the present invention, and are intended to enable those skilled in the art to understand the content of the present invention and implement it accordingly. They should not be construed as limiting the scope of protection of the present invention. All equivalent changes or modifications made in accordance with the spirit and essence of the present invention should be covered within the scope of protection of the present invention.
[0150] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
Claims
1. A method for preparing a catalytic packing material, characterized in that, Includes the following steps: (1) The packing carrier is loaded into the reaction equipment; (2) The epoxy resin solution is introduced into the reaction equipment and circulated, and discharged after circulation is completed, so that a liquid film is formed on the surface of the filler carrier. The epoxy resin solution contains solvent, magnetic material, epoxy resin, curing agent and first monomer. (3) Heating reaction causes the epoxy resin to crosslink and cure, forming an epoxy resin adhesive layer on the surface of the filler carrier; (4) The second monomer solution is introduced into the reaction equipment and circulated. After circulation is completed, it is discharged, so that a liquid film is formed on the surface of the epoxy resin adhesive layer. (5) The initiator solution is introduced into the reaction equipment to initiate the polymerization reaction and then discharged, wherein the initiator solution contains an initiator and a magnetic material; (6) Increase the temperature to ensure the polymerization reaction is complete; (7) Acid solution is passed into the reaction equipment to acidify and obtain a catalytic packing material with active catalytic components on the surface.
2. The method for preparing the catalytic packing material according to claim 1, characterized in that: The reaction equipment is a distillation column or a series of other equipment containers that can replace the distillation column to complete the packing transformation, the series of other equipment containers including one or more of tanks, pumps, constant temperature chambers, and drying chambers; and / or, the active catalyst component is one or more of polystyrene sulfonic acid and modified polystyrene sulfonic acid.
3. The method for preparing the catalytic packing material according to claim 1, characterized in that, The magnetic material is a magnetic nanomaterial; and / or, the first monomer is one or a combination of styrene and divinylbenzene; and / or, the second monomer is sodium p-styrene sulfonate; and / or, a modifier may be selectively added to the second monomer solution, the modifier being a hydrophilic monomer or a lipophilic monomer.
4. The method for preparing the catalytic packing material according to claim 3, characterized in that: The magnetic nanomaterial is one or a combination of magnetic ferrite materials, magnetic metals and their alloys; the modifier is one or a combination of methacrylic acid and polyethylene glycol.
5. The method for preparing the catalytic packing material according to claim 3, characterized in that: The magnetic nanomaterial is one or a combination of magnetic iron oxide, magnetic metals and their alloys; the modifier is one or a combination of methacrylic acid and polyethylene glycol.
6. The method for preparing the catalytic packing material according to claim 1, characterized in that: The material of the packing carrier is one or a combination of metal, plastic, ceramic, glass, fiberglass, and rubber, and the packing carrier is one or a combination of structured packing and random packing.
7. The method for preparing the catalytic packing material according to claim 6, characterized in that: The filler carrier is made of metal, and the preparation method further includes the steps of introducing a rust remover into the reaction equipment for rust removal and water washing before introducing the epoxy resin solution into the reaction equipment; and / or, The random packing is one or a combination of several of the following: Sital rings, Raschig rings, and triangular springs; the structured packing is one or a combination of several of the following: perforated corrugated plates, wire mesh, and helical springs.
8. The method for preparing the catalytic packing material according to any one of claims 1 to 7, characterized in that: The preparation method further includes step (3), in which the temperature of the heating reaction is 80-110℃, and during the heating reaction, the reaction equipment is purged with inert gas for more than 2 hours to allow the solvent to rapidly boil and evaporate to form an irregular surface; and / or, In step (6), the temperature of the heating reaction is 90-120°C. During the heating reaction, the reaction equipment is purged with inert gas for more than 7 hours to make the solvent boil and evaporate rapidly to form an irregular surface.
9. The method for preparing the catalytic packing material according to claim 8, characterized in that: In step (3), the purging time is 2-7 hours; and / or, in step (3), the inert gas is nitrogen; and / or, In step (6), the purging time is 7 to 12 hours; and / or, in step (6), the inert gas is nitrogen.
10. The method for preparing the catalytic packing material according to any one of claims 1 to 7, characterized in that: In step (2), the circulation time is 5–20 min, and the circulation is carried out at 50–70°C; and / or, calculated based on the packing height, the circulation time is 3–5 min / m, and the circulation is carried out at 50–70°C; and / or, In step (4), the circulation time is 5–20 min, and the circulation is carried out at 50–70°C; and / or, calculated based on the packing height, the circulation time is 3–5 min / m, and the circulation is carried out at 50–70°C; and / or, In step (5), after the initiator solution is discharged, the system is maintained at 50–70°C for 1–3 hours to react; and / or, In step (7), the acid solution is circulated into the reaction equipment, and the circulation time is 0.5 to 1 hour.
11. The method for preparing the catalytic packing material according to any one of claims 1 to 7, characterized in that: The preparation method further includes, after the cycle in step (2) is completed, purging the reaction equipment with inert gas at a temperature of 50–70°C for 1–5 minutes; and / or, The preparation method further includes, in step (4), after the second monomer solution is discharged, purging the reaction equipment with inert gas at a temperature of 50–70°C for 1–5 minutes; and / or, The preparation method further includes, in step (5), after the initiator solution is discharged, purging the reaction equipment with inert gas at a temperature of 50–70°C for 1–5 minutes; and / or, The preparation method further includes repeating steps (4) to (5) 2 to 3 times; and / or, The preparation method further includes step (7), in which water is introduced into the reaction equipment for washing after acidification is completed, the washing time is 10-30 min, and / or, calculated according to the height of the packing, the washing time is 10-30 min / m.
12. The method for preparing the catalytic packing material according to claim 1, characterized in that, In the epoxy resin solution, the epoxy resin content is 5-20% by mass, the first monomer content is 3-5% by mass, and the magnetic material content is 0.01-1% by mass; and / or, The second monomer solution contains 15-20% by mass of the second monomer, and also selectively contains 1-3% of a modifier; and / or, The initiator solution contains 0.01–1% magnetic material by mass; the initiator by mass content is 0.1–0.3%, and the initiator is a free radical initiator; and / or, The acid solution has a mass concentration of 3-5%, and the acid is one or a combination of several inorganic acids and strong organic acids; and / or The epoxy resin is one or a combination of bisphenol A type epoxy resin and phenolic epoxy resin; the curing agent is one or a combination of m-phenylenediamine and ethylenediamine; and / or... The epoxy resin solution uses ethanol as the solvent; and / or, The initiator solution uses ethanol as the solvent.
13. A method for converting a conventional distillation column into a catalytic distillation column, characterized in that: The step includes preparing the catalytic packing material in a distillation column using the method described in any one of claims 1 to 12.
14. A catalytic packing prepared by any one of claims 1 to 12 is used in a catalytic distillation process, wherein the catalytic distillation process includes hydrolysis reaction, transesterification reaction, esterification reaction, etherification reaction, alkylation reaction, isomerization reaction, acylation reaction, olefin addition reaction, olefin hydration reaction, and dehydration condensation reaction.
15. The application according to claim 14, characterized in that: The hydrolysis reaction includes the hydrolysis of esters into acids; the transesterification reaction includes the reaction of esters with alcohols to generate isoesters and isoalcohols.
Citation Information
Patent Citations
A method for preparing ceramic surface supported catalytic packing
CN113198535B
Supported catalytic filler and preparation method and application thereof
CN111013173A
Preparation method of supported catalytic filler for reactive distillation
CN114989484A